Antibiotic Intervention Affects Maternal Immunity During Gestation in Mice - Benner, Marilen; Lopez-Rincon, Alejandro; Thijssen, Suzan; Garssen, Johan; Ferwerda, Gerben; Joosten, Irma; van der Molen, Renate G.; Hogenkamp, Astrid (Frontiers in Immunology, 2021)
Background: Pregnancy is a portentous stage in life, during which countless events are precisely orchestrated to ensure a healthy offspring. Maternal microbial communities are thought to have a profound impact on development. Although antibiotic drugs may interfere in these processes, they constitute the most frequently prescribed medication during pregnancy to prohibit detrimental consequences of infections. Gestational antibiotic intervention is linked to preeclampsia and negative effects on neonatal immunity. Even though perturbations in the immune system of the mother can affect reproductive health, the impact of microbial manipulation on maternal immunity is still unknown. Aim: To assess whether antibiotic treatment influences maternal immunity during pregnancy. Methods: Pregnant mice were treated with broad-spectrum antibiotics. The maternal gut microbiome was assessed. Numerous immune parameters throughout the maternal body, including placenta and amniotic fluid were investigated and a novel machine-learning ensemble strategy was used to identify immunological parameters that allow distinction between the control and antibiotics-treated group. Results: Antibiotic treatment reduced diversity of maternal microbiota, but litter sizes remained unaffected. Effects of antibiotic treatment on immunity reached as far as the placenta. Four immunological features were identified by recursive feature selection to contribute to the most robust classification (splenic T helper 17 cells and CD5+ B cells, CD4+ T cells in mesenteric lymph nodes and RORγT mRNA expression in placenta). Conclusion: In the present study, antibiotic treatment was able to affect the carefully coordinated immunity during pregnancy. These findings highlight the importance of inclusion of immunological parameters when studying the effects of medication used during gestation.